APOC1 exacerbates renal fibrosis through the activation of the NF-κB signaling pathway in IgAN - Yu, Kuipeng; Ding, Lin; An, Xin; Yang, Yanjiang; Zhang, Xiaoning; Li, Luyao; Wang, Chunjie; Bai, Fang; Yang, Xiangdong (Frontiers in Pharmacology, 2023)
Abstract Introduction IgAN is the most common disease leading to end-stage renal disease, and tubular fibrosis represents an important risk factor for disease progression. However, research on the early molecular diagnostic indicators for tubular fibrosis and the mechanisms underlying disease progression is still lacking. Methods The GSE93798 dataset was downloaded from the GEO database. DEGs were screened and analyzed for GO and KEGG enrichment in IgAN. LASSO and SVM-REF algorithms were applied to screen for hub secretion genes. Expression and diagnostic efficacy of hub genes were confirmed by the GSE35487 dataset. Elias assay was applied to detect the expression of APOC1 in serum. Expression and localization of hub genes in IgAN were verified by expression of IHC and IF in human kidney tissues and correlation of expression with clinical data was verified in the Nephroseq Database. Finally, cellular experiments were clarified the role of hub genes on the signaling pathway. Results 339 DEGs were identified in the IgAN, including 237 up-regulated and 102 down-regulated. KEGG signaling pathway is enriched in ECM-receptor interaction, AGE-RAGE signaling pathway. APOC1, ALB, CCL8, CXCL2, SRPX2, TGFBI were identified 6 hub secretory genes by LASSO and SVM-REF algorithms. In vivo and in vitro experiments demonstrate that APOC1 expression was elevated in IgAN. The serum concentration of APOC1 is 1.232 ± 0.1812μg/ml in IgAN patients, whereas is 0.3956 ± 0.1233μg/ml in healthy individuals. APOC1 exhibits high diagnostic efficacy for IgAN(AUC = 99.091%, specificity = 95.455%, and sensitivity = 99.141%) in the GSE93798 dataset. APOC1 expression is negatively correlated with eGFR (R2 = 0.2285, P = 0.0385) and positively correlated with Serum creatinine (R2 = 0.41, P = 0.000567) in IgA nephropathy. APOC1 exacerbates renal fibrosis, possibly in part by activating the NF-κB pathway in IgAN. Conclusions APOC1 was identified as the core secretory gene of IgAN, which is closely associated with blood creatinine and eGFR and has significant efficacy in the diagnosis of IgAN. Mechanistic studies revealed that knockdown of APOC1 could improve IgAN renal fibrosis by inhibiting the NF pathway, which may be a potential therapeutic target for improving renal fibrosis in IgAN.